Strengthening Simarmata Youth Participation in Nation Building through Participatory Entrepreneurship Development in Simarmata Village, Samosir Regency - Jongkers Tampubolon; Jusra Tampubolon; Hengki Mangiring Parulian Simarmata (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2026)
This community service activity focuses on strengthening the participation of Simarmata youth (Generasi Muda Simarmata) in national development through participatory entrepreneurship development strategies. In the era of globalization, young people are expected not only to become beneficiaries of development but also to act as active agents of change within their local communities. However, limited entrepreneurial capacity, lack of practical exposure, and insufficient access to empowerment programs often hinder the optimization of their potential. This program was conducted from April 10–12, 2026, in Simarmata Village, Samosir Regency, involving approximately 300 participants representing Simarmata youth and interregional youth communities from various regions in Indonesia. The activity was implemented through interactive seminars and participatory discussions focusing on the strategic role of youth in nation-building and entrepreneurship development strategies. The results indicate a significant improvement in participants’ awareness, motivation, and understanding of entrepreneurship as a driver of economic and social transformation. More importantly, the program successfully strengthened the identity and role of Simarmata youth as a community-based development force, fostering collaboration, innovation, and sustainable economic initiatives. This study highlights that community-based participatory programs are effective in empowering local youth communities, particularly in enhancing entrepreneurial capacity and strengthening their contribution to sustainable national development.